(untitled) (Olhares, 2020)
The current article presents thoughts on certain aspects of improvisation in dance, on the blurred bounderies between life and art, dance and writing, body and space and among the arts. It approaches especially the so called Poetic Training and the establishing of improvisational process, according to the thinking of the dancers Dudude Herrmann and Lisa Nelson.